Managing Information Overload in a Pandemic: Influence of Social Media on Vaccine Attitudes in the Digital Age - Adekunle, Yusuf; Ogwezzy-Ndisika, Abigail O.; Ibraheem, Ismail A. (International Journal of Health Sciences, 2024)
Purpose: This study examined how social media influences public health decisions, focusing on how information overload during a pandemic impacts vaccine hesitancy and acceptance across demographics. It analyzed conflicting vaccine information to understand social media's role in shaping attitudes and identify strategies to mitigate its negative effects. Methodology: This study employed a multi-stage sampling method to gather data from diverse age groups, education levels, and occupations. This approach combines various techniques at different stages, making it suitable for large, geographically dispersed populations. By segmenting the population into manageable units, multi-stage sampling improves the accuracy, reliability, and representativeness of the data collected. Findings: The findings reveal that most respondents consider vaccine information on social media unreliable, underscoring the need for greater trust in online discussions. Many feel overwhelmed by conflicting messages, highlighting the necessity for clearer communication. Social media significantly shapes attitudes toward COVID-19 vaccines, with many shifting views after engaging with online content. Additionally, participants report mental health impacts from the constant stream of vaccine information, illustrating information overload. Unique Contributions to Theory, Policy and Practice: This study advances the information overload model by illustrating how excessive and conflicting vaccine information on social media disrupts comprehension and harms mental health. It emphasizes social media's role in shaping health attitudes and advocates for interdisciplinary approaches that incorporate psychological resilience into public health strategies. Findings highlight the need for regulations against misinformation to improve the credibility of online health information and promote trusted sources, particularly verified health organizations. The study also calls for health literacy initiatives to empower the public in navigating misinformation and suggests strategies for managing information overload through social media disengagement. Targeted initiatives that leverage trusted information sources can effectively combat vaccine hesitancy and boost community engagement in public health campaigns, ultimately improving health outcomes.